2023
DOI: 10.1186/s12888-023-04936-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of sleep quality and perceived stress on depressive symptoms among tertiary hospital nurses: a cross-sectional study

Abstract: Background Nurses in tertiary hospitals are at high risk for depression. Understanding sleep quality and perceived stress may contribute to nurses’ mental health and health-related nursing productivity. The aim of this study was to investigate the role of sleep quality and perceived stress on depressive symptoms among nurses in tertiary hospitals. Methods A total of 2,780 nurses (overall response rate = 91.1%) were recruited through a cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…Our study showed that nurses with lower educational level, lower income, more night shift work per week, more years of work, longer work hours per week, or working in the emergency department were more likely to have depressive symptoms, which is consistent with previous studies [ 2 , 5 , 43 , 44 ]. Our study also showed that contract nurses were more likely to experience depressive symptoms compare to the formal employee.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study showed that nurses with lower educational level, lower income, more night shift work per week, more years of work, longer work hours per week, or working in the emergency department were more likely to have depressive symptoms, which is consistent with previous studies [ 2 , 5 , 43 , 44 ]. Our study also showed that contract nurses were more likely to experience depressive symptoms compare to the formal employee.…”
Section: Discussionsupporting
confidence: 92%
“…Due to long work hours and high work pressure, nurses’ health is very likely to be negatively affected by depression [ 1 ]. Depression often involves a loss of interest in activities that were once enjoyable, feelings of worthlessness or guilt, difficulty sleeping, changes in appetite, and decreased energy or motivation [ 2 ], and the high prevalence of depressive symptoms among nurses has become a global problem [ 3 ]. Previous studies found that the prevalence of depressive symptoms among American nurses was 18% [ 4 ], while that among Chinese nurses was significantly higher, 48.83% [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several factors may contribute to this phenomenon. First, participants with anxiety, depression symptoms and poor sleep quality may experience great stress during their life, [27–30] and then result in the activation of sympathetic excitation, which was associated with the occurrence of CKD. Second, participants with these problems may cause endocrine disruption and changes in hormone levels, [31–33] which was associated with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…The Insomnia Severity Index (ISI) is a 7-item self-report questionnaire assessing the nature, severity, and impact of insomnia via a 5-point Likert scale during the "last month", yielding a total score ranging from 0 to 28 [47]. The total score was interpreted as follows: absence of insomnia (0-7); sub-threshold insomnia (8)(9)(10)(11)(12)(13)(14); moderate insomnia (15)(16)(17)(18)(19)(20)(21); and severe insomnia (22)(23)(24)(25)(26)(27)(28). The dimensions evaluated were severity of sleep onset, sleep maintenance, early morning awakening problems, sleep dissatisfaction, interference of sleep difficulties with daytime functioning, noticeability of sleep problems by others, and distress caused by sleep difficulties.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…According to a recent meta-analysis, the prevalence of sleep disturbances in Chinese nurses was 45.1% (CI 95%: 37.2-53.1%) [9], while Ielapi et al reported a prevalence of 65.4% [10]. Sleep disturbances can influence personal well-being and mental health, also causing depression [11], which has been reported in 60.3% of cases [12]. Furthermore, observational research has shown that a reduction in the time dedicated to sleep is associated with decreased productivity [13], quality of care, and patient safety [14].…”
Section: Introductionmentioning
confidence: 99%